EVALUATION IMPLEMENTATION OF BUDGET POLICYOPERATIONAL COST OF EDUCATION (BOP) IN STATE VOCATIONAL HIGH SCHOOL IN NORTH JAKARTA BIRTH YEAR BUDGET 2013 - Sodikin Sodikin; Thamrin Thamrin; Makruf Akbar (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2019)
The aim of this research is to find out the extent of implementation process about Educational Operating Cost (EOC) at Public Vocational High School in North Jakarta consists of; (1)rationality which underlying Public Vocational High School in North Jakarta (2) stages (3)the main contents implementation of budget policy of Educational Operating Cost. (4) budget policy and (5) the impact of the implementation of Educational Operating Cost policy.This research uses qualitative methods with observation, interview and documentation. In this case the right approach and considered applicable is to use Countenance of Robert E. Stake because this model is considered to provide an overview in the beginning of evaluation results to the evaluation criteria of policy implementation. Stake stressed that there is two basic activities in the evaluation of Description and Judgement which emphasizes three stages such as; Antecedents (Context), Transaction (Process), Outcomes (Output), as this model has more advantages than the other methods.The research carried out at Public Vocational High School in North Jakarta consisting of 8 (eight) schools. The impact of expected implementation policy evaluation is : School can implement message contents of Government Rule Number. 34/2015 which generally aims to fund education operational activity in order to implement compulsory education 12 years. to complement the needs of teaching and learning activities, to maintain educational facilities, and to improve the management of the school administration.